A systematic review of modest fashion perspectives in the Malaysian fashion industry / Zulina Kamarulzaman and Nazlina Shaari - Kamarulzaman, Zulina; Shaari, Nazlina (Faculty of Art and Design, 2023)
Modest fashion has become popular over the last decade and is promoted as the latest dressing style. Modest fashion is usually mistaken for Islamic wear, specifically in the Malaysian fashion industry. Malaysians' acceptance of the Islamic lifestyle started long ago, with the continuous adaptation of multiculturalism. This paper aims to determine modest fashion in the context of the Malaysian fashion industry. A systematic review of the published articles and literature was conducted to outline the concept of modest fashion and the relevant issues in modest fashion perspectives. The study identified five innovative components in its conceptual framework: beliefs, fashion expertise, management of business relationships (BRM), fashion culture, and social media influencers originating from modest fashion. The conceptual framework also included related keywords from past research. The findings in this study indicated a positive relationship between modest fashion and faith practices in Islam. The results implied a need for future research to study the acceptance of modest fashion as a dressing style among non-Muslim consumers in Western countries. This paper concludes that modest fashion has evolved into one of the mainstream fashion lines in the fashion world and is no longer seen as a conservative style of fashion.